Etika Bisnis Syariah di Tengah Perkembangan E-Commerce: Kajian Kualitatif dari Literatur Islam - Anjelina, Juwita; Muzan, Amrul (Al-Maqashid: Journal of Economics and Islamic Business, 2025)
This research explores the application of sharia business ethics in rapidly growing e-commerce. Although e-commerce makes transactions easier, it presents challenges to ensure compliance with sharia principles such as honesty, fairness and transparency. This study uses a qualitative approach based on Islamic literature to identify technologies such as blockchain and sharia fintech proposed to reduce the risk of sharia violations. This research emphasizes the importance of strict regulations, effective supervision, and the application of sharia values ​​in e-commerce to increase consumer trust and create a sustainable business ecosystem in accordance with Islamic teachings.